Olfactory communication : chemical characterization of the ventral gland and supplementary sacculi secretions of the dwarf hamster, Phodopus sungorus sungorus - Smit, Denice (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1997.